Futebol, performatividade e neoliberalismo: reconfiguração identitária do Manchester United diante do mercado - Oliveira, Jonas Jandson Alves (2019)
In the first semester 2017, Manchester United, the current richest team in the world (BBC, 2018), has officialized a partnership with a Non-governamental Organization from The United Kingdom called Stonewall. The focus of this aliance aimed at the development of campaigns and actions on behalf of the LGBT cause in the framework of football and it also searched for broadening of this acting to Premier League, the first tier of the English champioship. This work seeks analyzing how performativity influences the identitary traces that the club creates and reconfigures throughout time. The choice of this theoretical scenario for the development of the research deals with the perspective of Pennycook (2014) based on the philospher Judith Butler, to whom performativity sets as a characteristic of a somatic turn that attains the social sciences and the applied linguistics. The main objective of this dissertation is the analysis of processes that take this team, a modelo f management inside and outside the pitch for other clubs around the world, to no longer sustain itself in a pre-formed identity, being it performed daily and dialogically intermediated by the current discourses. More specifically, I investigate the accession of the English club in actions related to the gender policies and exploit, socio-historically, its rise to the threshold of a club/company in which it is these days through bibliographical productions as the source of theorization and documental analysis of written, imagetic and audiovisual documental sources from the wbsite of Manchester United, as well as from the online versions of Brazilian and foreign sport tabloids and newspapers. Throughout the work I demonstrate how the clube has modified itself and searches to affirm a new identity resorting to the maintenance of a good image towards the social view without getting rid of its neoliberal agenda.